Analisis Waste of Administration pada Aktivitas Pergudangan: Studi Kasus Gudang Persediaan PT XYZ - Rahma Nur Khoiru Nisa; Wiku Larutama (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
Administrative activities at PT XYZ’s warehouse are still performed manually, such as recording and verifying physical documents, which leads to delays, data duplication, and operational inefficiencies. This situation indicates the presence of administrative waste that slows down warehouse operations. This study aims to identify and analyze this administrative waste in order to improve work process efficiency. The approach used was a qualitative descriptive method through direct observation of goods receipt and issuance activities, with analysis using Root Cause Analysis (RCA) and the 5 Whys Analysis to identify the root causes of the problems. The results of the study indicate that waste occurs due to the lack of an integrated digital administrative system and the low technological proficiency of employees. Therefore, it is recommended that administrative processes be digitized and that digital skills training be provided to create more efficient work processes.